2009
DOI: 10.1111/j.1467-646x.2009.01034.x
|View full text |Cite
|
Sign up to set email alerts
|

Pecking Order Behavior in Emerging Markets*

Abstract: This paper examines the validity of the pecking order hypothesis in 23 emerging market countries. Emerging market countries would appear to be an ideal setting for the pecking order hypothesis to hold because of the presence of strong asymmetric information issues and agency costs. We observe, however, little support for the pecking order hypothesis as the primary financing theory for all emerging market firms. Firms in these countries finance their deficit mainly with equity, the opposite of what would be exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(6 citation statements)
references
References 71 publications
2
3
0
Order By: Relevance
“…These findings reveal that the financial deficit explains no more than half of the issued debt, which clearly does not validate the pecking order theory in Latin American markets. The POT F-test reaches the same conclusion and coincides with other studies conducted in emerging markets (Seifert & Gonenc, 2010;Chakraborty, 2013;Chen et al, 2013;Kannadhasan et al, 2018;Nguyen et al, 2019).…”
Section: Capital Structure Decision and Error Correction Modelsupporting
confidence: 89%
See 1 more Smart Citation
“…These findings reveal that the financial deficit explains no more than half of the issued debt, which clearly does not validate the pecking order theory in Latin American markets. The POT F-test reaches the same conclusion and coincides with other studies conducted in emerging markets (Seifert & Gonenc, 2010;Chakraborty, 2013;Chen et al, 2013;Kannadhasan et al, 2018;Nguyen et al, 2019).…”
Section: Capital Structure Decision and Error Correction Modelsupporting
confidence: 89%
“…The pecking order theory has also been studied in emerging markets. Seifert and Gonenc (2010) studied companies from 23 emerging countries between 1985 and 2004. Their results showed that the pecking order theory was not fulfilled, despite the greater information asymmetries in these countries.…”
Section: The Trade-off and Pecking Order Theoriesmentioning
confidence: 99%
“…Additionally, firms in emerging markets suffer from a lack of wide media and analyst coverage, consistent with the theoretical work of Merton (1987) and Arbel et al (1983). In light of the aforementioned studies, the present study hypothesizes that whether the ESG-rated firm's domestic equity market is classified as emerging or developed affects its visibility, as ESG-rated firms in emerging markets better avoid public scrutiny, consistent with research on traditional equities in emerging markets (see for example Bauman, 1989;Seifert & Gonenc, 2010).…”
Section: Hyp Othe S E Ssupporting
confidence: 80%
“…More information asymmetry exists between managers and shareholders of multinational firms. Seifert and Gonenc (2010) examine the validity of the pecking order hypothesis in 23 emerging market countries. They find no support for the pecking order for firms in emerging markets suffering the most from asymmetric information issues or agency costs.…”
Section: Resultsmentioning
confidence: 99%